Peningkatan Kesejahteraan Melalui Kemandirian Petani Dalam Pengelolaan Integrasi Sawit Sapi Berkelanjutan - Sulistiawati, Rini; Kusrini, Novira; _, Imelda (Jurnal Ekonomi Kuantitatif Terapan; 2018: Vol. 11, No. 2, Agustus 2018 (pp. 147-253), 2018)
Integration of palm oil plantation with cattle can provide advantages in both sub sectors which will increase the income and welfare of farmers. The implementation of the integration palm cattle must be supported by appropriate management practices so that the resulting production can be more efficient, competitive and sustainable. The population in this research is all farmers which have already implemented palm cattle integration. The samples of these researches are 150 respondents. This research using Structural Equation Model (SEM) that is multivariate statistic procedure using AMOS software. The results showed that the increase in prosperity of palm cattle integration farmers can be done with increased self-reliance of farmers through the management and coaching in the sustainable integration of palm cattle. Palm cattle integration farmers will have a competitiveness if it is able to utilize the resources extension workers, share knowledge and take advantage of training opportunities. Farmers also need to be able to make decisions, develop a plan for managing the integration of the palm cattle and managed to create a quality production.
Keywords: integrasi sawit sapi, kesejahteraan, kemandirian, Structural Equation Model, statistik multivariat